Correlation between gene mutation status and clinicopathologic features in early multiple primary lung cancer - Teng, Fei; Xu, Jian; Wang, Jian; Yang, Bo; Wu, Yong-Zhong; Jiang, Yue-Quan; Wang, Zhi-Qiang (Frontiers in Oncology, 2023)
Objective To understand the characteristics of genetic mutation in multiple primary lung cancer so as to guide clinical decisions in targeted therapy. Methods We analyzed a total of 265 tumors from 111 patients who underwent surgery for multiple lung cancers. Individual tumors were subjected to histological evaluation and gene mutation analysis using ABI 7500 Fluorescence quantitative PCR. Results In this study, we analyzed demographic and clinical parameters such as age, gender, smoking, alcohol consumption, pathological type, number of nodules, and other details of 111 patients with early multiple primary lung cancer. We also compared the clinicopathologic characteristics of different populations based on the gene mutation status of pulmonary nodules. Subsequently, we performed a clinicopathological analysis of all 265 pulmonary nodules from these patients. Results showed significant differences in clinicopathological features of pulmonary nodules in different genetic mutations. Conclusion This study revealed the gene mutation characteristics and clinicopathological features in early multiple primary lung cancer. We found that the gene mutation status between different nodules in patients with early multiple primary lung cancer was inconsistent in most cases. Therefore, the use of targeted therapy based on the genetic sequencing of only one nodule, is unreliable. We hope this study can be helpful in guiding clinical treatment decisions.